Novel neurotrophic treatments in rats and toxin sensitivity of genetically modified mice in the unilateral 6-OHDA model of Parkinson's disease - Piltonen, Marjo (Dissertationes Biocentri Viikki Universitatis Helsingiensis, ISSN 1799-7372, 2012)
Tiivistelmä suomeksi.
Keywords: Parkinsonin tauti; lääkeaineet; hermomyrkyt; dopamiini; hermosolut; kasvutekijät; eläinkokeet; rotat (suku); hiiret; Parkinsons sjukdom; eläinmalli; hermokasvutekijä